(3GdeQLY GdeJcGed aj GOGQI GdGSJQGJjLjI (B/s - (3LhGO, Thbj fGLjs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2009)
(3GdeONd Edi GOGQI GdGSJQGJjLjI , GdGSS GdacQjI h GdGWQ GdacQjI ddSjGSI h GdGSJQGJjLjI , eaghe GOGQI GdGSJQGJjLjI , GdHjFI h GOGQI GdGSJQGJjLjI , UjGZI GdGSJQGJjLjI GdGOGQjI , GNJjGQ h JfajP GdGSJQGJjLjI GdGOGQjI , Jbjje h QbGHI GdGSJQGJjLjI GdGOGQjI , eXGgQ GOGQI GdGSJQGJjLjI (B.s
(3eQGLY U(B.389s
Keywords: (3EOGQI GdGYeGds; (3GdEOGQIs; (3Jbjje GdCOGAs